Strategi Badan Pendapatan Daerah dalam Peningkatan Tahunan Pajak Reklame terhadap Pendapatan Asli Daerah (PAD) di Kabupaten Sikka - Ananias Luis Ga’a; Andreas Rengga; Viktor Eko Transilvanus (Dharma Ekonomi, 2024)
Advertising tax is one of the significant sources of Local Revenue (PAD) in Sikka Regency, contributing up to 25% of the total PAD. This study discusses the strategies implemented by the Sikka Regency Regional Revenue Agency (BAPENDA) to increase advertising tax revenue annually. These strategies include digitalization of administrative services, intensive socialization to the community, strict law enforcement, and collaboration with related agencies such as Satpol PP and the Prosecutor's Office. The results of the study indicate that optimization of advertising tax revenue can be achieved through simplification of the administrative process, technology-based supervision, and revenue diversification by utilizing the potential of digital advertising. Supporting factors include proactive policies of the local government, while the main inhibiting factors are low taxpayer compliance and lack of socialization. Through a collaborative approach, innovation, and law enforcement, advertising tax is expected to provide a greater contribution to Sikka Regency's PAD, support regional development, and create a more modern, transparent, and sustainable tax management system.